Violência Contra Pessoa Idosa: um estudo de representações sociais - Alves, Karoline de Lima (2016)
The reality we are experiencing today, about the increase in the elderly population and its impacts arising from this phenomenon in the various fields of society, proven and discussed by academic and scientific society, is an important factor in understanding the concept of successful aging, Risk of diseases and their physical and mental integrity, in addition to their guaranteed rights, thus being interested in the issue of violence against the elderly, using the theoretical framework of Theory of Social Representations as a tool in the identification of cognitive, affective, social aspects And symbolic of the knowledge of common sense, through social communication and interaction, allows the expression of individuals' positions on this phenomenon in the context where they are inserted. In this sense, the study aimed to know the social representations about violence against the elderly in various age groups. It is an exploratory study, with a quantitative-qualitative approach, carried out with 150 subjects of both sexes, located in the city of João Pessoa-PB / Brazil. From this research two articles were presented in the results. The first article sought to characterize the production of national health articles, in the temporal cut of the last 5 years, available in the LILACS database of the Virtual Health Library, using as keywords the words: "violence and elderly"; And "social representations and violence". Of the 108 units found, 59 units were considered in the first descriptor, and in the second descriptor 21 units were found and only 19 units were evaluated, using the Social Representation Theory in their investigations , For both descriptors, those that met the established inclusion criteria were analyzed: articles in Portuguese, available in full and mentioning the expressions according to the descriptors, either in the title or in the abstract. The second article sought to apprehend the social representations about violence against the elderly in various age groups. This is an exploratory study, with a quantitative-qualitative approach. At the beginning of this study, the Free Words Association Technique was formed by the term "violence against the elderly". Then a positioning table regarding the types of violence and the sociodemographic questionnaire, where the data were processed by the software Iramuteq version 0.7 alpha 2 and Statistical Package for Social Sciences version 2.0 and analyzed in light of Theory of Social Representations. The results of the study show the construction of social representations about violence against the elderly, so it is important to highlight other psychosocial conditions related to the demographic distribution of the symbolic repertoire referring to the object represented, according to some groups of society, to produce and communicate a knowledge / practice About the violence committed to this population, and finally, in view of these images, or representations, end up supporting social practices. It is hoped that this study contributes to the professionals subsidizing the strengthening of public policies aimed at the elderly population